African traditional leadership and succession in the post-colonial Shona novel. Issue 2 (4th May 2017) - Makaudze, Godwin
ABSTRACT: African institutions of leadership and succession have received vehement attacks from colonial and early Shona writers. African leadership was presented as tyrannical, egocentric, immoral, and barbaric; and was condemned as lacking normal checks and balances. Colonialism on the other hand was offered as the panacea for the purported political upheaval. Using the post-colonial literary theory, this paper examines the portrayal of Shona traditional leadership and succession by two post-colonial Shona writers. It examines how realistic their expositions are and how different they are from early and colonial fiction about the same. The paper concludes that recent portrayals by Shona writers approximate Shona practice and are quite different, if not an anti-thesis of colonial literature about the same.